High-Performance Pentacene/ZnO UV-Visible Photodetector Using Solution Method - Srivastava A.; Jit S.; Tripathi S. (My University, 2025)
This work reports a Pd/AlO/ZnO/pentacene/ PEDOT:PSS/indium-doped tin oxide (ITO) structure-based high-performance ultraviolet (UV)-visible photodetector fabricated on an ITO substrate. The poly(3,4-ethylene dioxythiophene) polystyrene sulfonate (PEDOT:PSS) acts as the hole transport layer (HTL), while aluminum oxide (AlO) acts as a hole blocking layer (HBL) to reduce the dark current. At -1 V bias voltage, the proposed device shows the responsivity, sensitivity, detectivity, and external quantum efficiency (EQE) of 25.51 A/W, 2574.19, 1.52 \times 10^{16} Jones, and 10171% at 311 nm (UV region) while the corresponding values at 565 nm (visible region) are found to be 0.36 A/W, 346.66, 2.17 \times 10^{14} Jones, and 79.65%, respectively. © 1963-2012 IEEE.